3'-Terminal sequence of wheat mitochondrial 18S ribosomal RNA: further evidence of a eubacterial evolutionary origin. - Schnare, M N (1982)
We have determined the sequences of the 3'-terminal approximately 100 nucleotides of [5' -32P]pCp-labeled wheat mitochondrial, wheat cytosol, and E. coli small sub-unit rRNAs. Sequence comparison demonstrates that within this region, there is a substantially greater degree of homology between wheat mitochondrial 18S and E. coli 16S rRNAs than between either of these and wheat cytosol 18S rRNA. Moreover, at a position occupied by 3-methyluridine in E. coli 16S rRNA, the same (or a very similar) modified nucleoside is present in wheat mitochondrial 18S rRNA but not in wheat cytosol 18S rRNA. Further, E. coli 16S and 23S rRNAs hybridize extensively to wheat mitochondrial 18S and 26S rRNA genes, respectively, but wheat cytosol 18S and 26S rRNAs do not. No other mitochondrial system studies to date has provided comparable evidence that a mitochondrial rRNA is more closely related to its eubacterial homolog than is its counterpart in the cytoplasmic compartment of the same cell. The results reported here provide additional support for the view that plant mitochondria are of endosymbiotic, specifically eubacterial, origin.